2007
DOI: 10.1002/j.2161-1874.2007.tb00028.x
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Recovering and Nonrecovering Substance Abuse Counselors' Belief Systems

Abstract: This study investigated recovering and nonrecovering substance abuse counselors' beliefs about the etiology and treatment of substance abuse disorders. Qualitative methods were used to investigate these variables. Analysis of the data revealed several key findings with implications for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Our findings related to the use of recovery experience in programmatic decisions are consistent with the study of Crabb and Linton (2007) who found that some service providers with preference for the use of the 12-step model of recovery did not believe that available research evidence enhanced their existing knowledge but rather only validated what they already knew. Similarly, symbolical use of evidence-based practice, in which decision makers use the evidence to confirm their beliefs and the programmatic decisions they had already made, was observed in government agencies across education, health, and social services (Amara, Ouimet & Landry, 2004;Milner, Estabrooks, & Humphrey, 2005) as well as in addiction agencies serving women (Jack et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings related to the use of recovery experience in programmatic decisions are consistent with the study of Crabb and Linton (2007) who found that some service providers with preference for the use of the 12-step model of recovery did not believe that available research evidence enhanced their existing knowledge but rather only validated what they already knew. Similarly, symbolical use of evidence-based practice, in which decision makers use the evidence to confirm their beliefs and the programmatic decisions they had already made, was observed in government agencies across education, health, and social services (Amara, Ouimet & Landry, 2004;Milner, Estabrooks, & Humphrey, 2005) as well as in addiction agencies serving women (Jack et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Crabb and Linton (2007) studied the belief systems of recovering and nonrecovering substance abuse counselors. This qualitative study included eight counselors, all of whom had a relevant graduate degree and at least 5 years of clinical experience.…”
Section: Clinical Supervision In the Substance Abuse Treatment Fieldmentioning
confidence: 99%
“…These findings indicate that advanced education and training for clinical supervisors are necessary to address the individual differences found in supervisees. Crabb and Linton (2007) studied the belief systems of recovering and nonrecovering substance abuse counselors. This qualitative study included eight counselors, all of whom had a relevant graduate degree and at least 5 years of clinical experience.…”
Section: Clinical Supervision In the Substance Abuse Treatment Fieldmentioning
confidence: 99%
“…First, counselor educators should refrain from making assumptions about a field supervisor's clinical approach based on that person's educational and personal background. A study by Crabb and Linton (2007) suggested that master's‐level addictions counselors who are not in recovery from a substance misuse problem may adhere more rigidly to 12‐step treatment models than their recovering, less credentialed counterparts. These findings run contrary to the popular view held in the field that counselors who are less educated and in recovery adhere more fervently to 12‐step‐based treatment models.…”
Section: Recommendationsmentioning
confidence: 99%